Maternal & child health nursing : care of the childbearing & childrearing family - Pillitteri, Adele ([Place of publication not identifed] : Wolters Kluwer Health, 2007)
Introduction to maternal-child nursing helps you understand wellness and illness as family-centered events.
Unit I: Maternal and child health nursing practice -- Unit II: The nursing role in preparing families for childbearing and childrearing -- Unit III: The nursing role in caring for the pregnant family -- Unit IV: The nursing role in caring for the family during labor and birth -- Unit V: The nursing role in caring for the family during the postpartal period -- Unit VI: The nursing role in health promotion for a childrearing family -- Unit VII: The nursing role in supporting the health of ill children and their families -- Unit VIII: The nursing role in restoring and maintaining the health of children and families with physiologic disorders -- Unit IX: The nursing role in restoring and maintaining the health of children and families with meantal heslth disorders
Includes bibliographical references.
Keywords: MATERNITY NURSING